2011
DOI: 10.1186/1471-2180-11-54
|View full text |Cite
|
Sign up to set email alerts
|

Antistaphylococcal and biofilm inhibitory activities of acetyl-11-keto-β-boswellic acid from Boswellia serrata

Abstract: BackgroundBoswellic acids are pentacyclic triterpenes, which are produced in plants belonging to the genus Boswellia. Boswellic acids appear in the resin exudates of the plant and it makes up 25-35% of the resin. β-boswellic acid, 11-keto-β-boswellic acid and acetyl-11-keto-β-boswellic acid have been implicated in apoptosis of cancer cells, particularly that of brain tumors and cells affected by leukemia or colon cancer. These molecules are also associated with potent antimicrobial activities. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 47 publications
1
100
2
2
Order By: Relevance
“…The resistance of some of the Gram-negative bacteria could be due to the more hydrophilic outer membrane containing lipopolysaccharide (LPS), and the outer membrane acting as a penetration barrier for macromolecules and hydrophobic compounds (Nikaido, 1996). Raja et al (2011) reported that the lack of antibacterial activity of active compounds of Boswellia sp. against Gramnegative bacteria might be attributed due to the presence of lipophilic outer membrane in Gram-negative, which composed primarily of lipopolysaccharide molecules and forms hydrophilic permeability barrier providing protection against the effects of highly hydrophobic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance of some of the Gram-negative bacteria could be due to the more hydrophilic outer membrane containing lipopolysaccharide (LPS), and the outer membrane acting as a penetration barrier for macromolecules and hydrophobic compounds (Nikaido, 1996). Raja et al (2011) reported that the lack of antibacterial activity of active compounds of Boswellia sp. against Gramnegative bacteria might be attributed due to the presence of lipophilic outer membrane in Gram-negative, which composed primarily of lipopolysaccharide molecules and forms hydrophilic permeability barrier providing protection against the effects of highly hydrophobic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococci have the ability to form biofilms on an implanted medical device or damaged tissues and these biofilms are difficult to eradicate. 21 The highest antibiofilm activity documented for ethanol 80% extract 95.2% and ethyl acetate extract 93.9% against Staphylococcus aureus, while the lowest documented for ethanol 80 % extract 55.4 % and ethyl acetate extract 59.3% against Streptococcus mitis (Table 3 and 4). However, none of the extracts was able to inhibit biofilm formation completely this may be due to solubility and diffusion of phytochemical constituents in agar media.…”
Section: Anti-biofilm Activity Of Seed Extractsmentioning
confidence: 99%
“…21 Twofold serial dilutions of plant extract were made in sterile 96 flat wells microtiter plates containing 100 μl of Nutrient broth per well. The tested concentration ranged from (0.4883-62.5) mg/ml for ethanol 80 % and ethyl acetate fraction.…”
Section: Determination Of Antibiofilm Activitymentioning
confidence: 99%
“…This is due to the presence of lipophilic outer membrane in Gram-negative bacteria, which acts as a hydrophilic permeability barrier for the entry of hydrophobic compounds such as AKBA (Raja et al 2011;Hancock 1997;Helander et al 1998). Similar observations were made in studies dealing with antibacterial activity of other hydrophobic compounds against Gram-negative bacteria (Trombetta et al 2005;Gallucci et al 2009).…”
Section: Minimum Inhibitory Concentrationmentioning
confidence: 99%